Nizaya götüren cehâlet veya garar sebebiyle fâsid olan akitlerin sahihe dönüştürülmesi ve “sulbü’l-akit” kavramı - Bölükbaş, Ali Haydar; Kumaş, Ali (İstanbul Sabahattin Zaim Üniversitesi, 2020)
Bu makalede, fesâd nazariyesi içerisinde cehâletten kaynaklanarak fâsid kabul edilen akitlerin sahihe dönüştürülmesi ile ilgili hususlar ve sulbü’l-akit kavramı, ayrıntılı fürû örnekleri üzerinden işlenmiştir. Konu, içerik analizi yöntemi kullanılarak ele alınmıştır. Fesâd, Hanefî fıkıh düşüncesinin ortaya çıkardığı, diğer mezheplere göre geçersiz kabul edilen birçok akit türünden işlemi sahihe çevirebilme olanağı veren bir kavramdır. Bu kuralın altında yatan ana düşünce, akitlerin sahihe çevrilebilmesidir. Akitlerin sahihe çevrilmesiyle ilgili pek çok ayrıntı söz konusudur. Hukukî işlemlerde fesâd gerekçeleri arasında en çok karşılaşılan şekil, akdin unsurlarındaki bilinmezliğin (cehâlet) tarafları anlaşmazlığa sürüklemesidir. Hanefî fıkhında, cehâlet barındıran akitlerde meydana gelen veya gelebilecek olan anlaşmazlıkları önleyip akitleri sahihe çevirme hususunda belirleyici olan sulbü’l-akit kavramının zaman içerisinde geliştiğini gözlemlemek mümkündür. Akitlerin sahihe çevrilmesi, cehâletin akitte bulunduğu konuma göre değişiklik göstermektedir. Akdin sulbünde olan fesâd, güçlü fesâd (el-fesâdü’l-kavî); akdin sulbünde olmayıp onun bazı vasıf ve şartlarında olan fesâd ise zayıf fesâd (el-fesâdü’d-da‘îf) olarak ele alınır. Bu bağlamda akitlerin sahihe dönüştürülmesinde sulbü’l-akit kavramı belirleyici bir konumdadır.

In this article, the principle of sulb al-akit is initially addressed within the context of fasād theory. In the second instance, the conversion of invalid contracts resulted from obscurity into valid contracts is elaborated in a detailed way, introducing some legal precedents that includes the application of the principle of sulb al-akit. The subject has been discussed using the content analysis method. Fasād is a principle that is formed by the Ḥanafī fiqh (jurisprudence) and provides possibility to turn many contractual transactions that are considered invalid according to other madhhabs (legal schools) into sahih (valid). There are many details about the application of this principle since the main idea of this principle is the ability to transform contracts from invalid to valid. Within the border of legal procedures, the most common among fasād justifications (defect justification) is the obscurity in the contractual elements that leads the parties to disagreements. In order to resolve disagreements and conflicts that occur or may occur in these contracts, it is possible to observe the development of the principle of sulb alakit within the Ḥanafī fiqh in time. The transformation of concluded contracts from valid to invalid demonstrates variety according to the circumstances of the obscurity in the contracts. Fasād is examined in two ways: one is fasād kavī (strong defect) that is within the basic elements (sulb al-akit) of contracts and the other is fasād ḍa‘īf (weak defect) that exists within the characteristics and conditions of contracts. In this regard, the principle of sulb al-akit is the decisive factor to categorise fasād in contratcs and turn them into valid contracts.
Transformation of contract to be validated at the end of ignorence (jahalah) or gharar leading parties of contract to conflict (niza‘) and the concept of sulb al-akid
« ص لب لعاقد » تصح يح ا لعقود ا لفاسد ةب س بب ا لجهالة أو الغرر مم ا يؤ د إيلى لنزاا ع ومفه
Keywords: İslâm hukuku; Fâsid-fesâd; Cehâlet-garar; Niza (anlaşmazlık/çekişme); Tashîh; Sulbü; Islamic law; Fāsid-fasād; Sulb al-akit; Jahalah-gharar; Dispute/disagreement (niza‘); Tashih; ﺣﻘﻮق اﻹﺳﻼم; ﻓﺎﺳﺪ-ﻓﺴﺎد; ﺟﻬﺎﻟﺔ-ﻏﺮر; ﻧﺰاع; ﺗﺼﺤﻴﺢ; ص لب العقد